The spirit level. Why equality is better for everyone - Wilkinson, Richard G.; Pickett, Kate (New York, 2010)
"The book details the "pernicious effects that inequality has on societies: eroding trust, increasing anxiety and illness, (and) encouraging excessive consumption." Based on thirty years of research, it claims that for each of eleven different health and social problems: physical health, mental health, drug abuse, education, imprisonment, obesity, social mobility, trust and community life, violence, teenage pregnancies, and child well-being, outcomes are substantially worse in more unequal rich countries. Statistics are given for 23 of the top 50 rich countries and also for 50 states of the United States of America. The book contains extensive graphs and charts, also available online."